Aplikasi Manajemen Pelayanan Gereja Berbasis Android - Priska Rusalno Sutanto; Henry Novianus Palit; Andreas Handojo (Jurnal Infra, 2017)
Currently, most of the management systems for church services are still manuals using paper or using social media. This can be one of the causes of paperlessness and when providing information related to services through social media such as BBM, Whatsapp, and Line often the concerned church officer forgets the scheduled task beforehand. This app is made based on mobile apps because now the use of the smartphone has become one of the needs for its users. This supports the use of applications that are easy to access by the church officer because it is in the smartphone used in daily life.Given the notification on the application can make it easier for church officials to know information related to church service activities and this application can help the church service management system more regularly because it has been incorporated in an application that utilizes android technology based mobile apps.